Implementasi Manajemen Bandwidth Load Balancing Equal Cost Multi-Path - Bagus Hidayat; Ari Wibowo (Fakultas Teknik Universitas Pancasila, 2022)
The internet network often experiences disturbances due to the large amount of bandwidth usage because it is not regulated properly. This paper details the deployment of multi-path equal cost load balancing bandwidth management to integrate two Internet service providers. The Network Development Life Cycle (NDLC) approach is employed in this study. Analysis, design, simulation prototype, implementation, monitoring, and management are all part of the process. Combining two ISPs, according to the findings of this study, is intended to maximise internet consumption from both ISPs. The ability of one ISP to share traffic equitably is merely one consideration when it comes to load balancing.